Taurine in Septic Critically Ill Patients: Plasma versus Blood - Ata Mahmoodpoor; Afsaneh Farjami; Niloufar Farzan; Hamed Hamishehkar; Parina Asgharian; Sarvin Sanaie; Kamran Shadvar; Farnaz Naeimzadeh; Hadi Hamishehkar (Tabriz University of Medical Sciences, 2023)
Purpose: Sepsis and systemic inflammatory response syndrome (SIRS) encompass various problems throughout the body, and two of its major problems are the creation of oxidative substances in the body and decrease of the body's antioxidant capacity to deal with the stress and organ damage. Optimal enteral nutrition fortified with antioxidant or immunomodulator amino acid is a hot topic concerning sepsis in the critical care setting. Taurine plays a protective role as an antioxidant in cells that is likely to have a protective role in inflammation and cytotoxicity. Methods: In the present study, 20 septic patients and 20 healthy volunteers were enrolled. The blood and plasma taurine levels of the patients on days 1, 3 and 7 were measured. Blood and plasma taurine level and the correlation between them, organ failure, and severity of the disease were assessed. Results: Taurine concentrations in the plasma of the septic patients were significantly lower than control group, and the whole blood concentrations were significantly higher than those of the control group (P<0.001). There was not a significant correlation between the blood and plasma taurine levels in control and septic patients. In addition, there was not any correlation between the severity of the disease, organ failure, mortality, and plasma as well as the blood concentration of taurine. Conclusion: In septic patients, taurine concentration in plasma and blood are low and high, respectively. These concentrations are not linked to each other and not associated with the patients' outcome, and the disease severity, and organ failure.